(untitled) (Modern education and development, 2024)
Diabetes mellitus, commonly referred to as diabetes, is one of the most widespread chronic diseases, even in the most developed countries. The number of affected individuals continues to increase year by year. This disease is classified as an endocrine disorder, caused by the complete or partial deficiency of the hormone insulin. It is characterized by hyperglycemia, which is the prolonged elevation of glucose levels in the blood. The disease disrupts various metabolic processes (carbohydrate, lipid, protein, mineral, and water-electrolyte metabolism). According to recent studies, the global prevalence of diabetes has doubled every 12–15 years. According to the International Diabetes Federation, nearly 430 million people worldwide suffer from diabetes, with the majority suffering from Type 2 diabetes. By 2040, it is projected that the number of diabetes patients will reach 642 million, with 540,000 of them being children under 14. In Uzbekistan, over 257,000 people have diabetes, of which over 2,300 are children and 913 are adolescents. Diabetes can lead to complications such as kidney failure, blindness, myocardial infarction, stroke, and gangrene, sometimes resulting in amputations. This remains a critical issue that requires ongoing research.